Pinhole-free perovskite films for efficient solar modules. Issue 2 (13th January 2016) - Qiu, W.; Merckx, T.; Jaysankar, M.; Masse de la Huerta, C.; Rakocevic, L.; Zhang, W.; Paetzold, U. W.; Gehlhaar, R.; Froyen, L.; Poortmans, J.; Cheyns, D.; Snaith, H. J.; et al.
Abstract : We demonstrated a 4 cm 2 aperture area perovskite solar module with a PCE of 13.6% and a geometrical fill factor of 91%. Abstract : We report on a perovskite solar module with an aperture area of 4 cm 2 and geometrical fill factor of 91%. The module exhibits an aperture area power conversion efficiency (PCE) of 13.6% from a current–voltage scan and 12.6% after 5 min of maximum power point tracking. High PCE originates in pinhole-free perovskite films made with a precursor combination of Pb(CH3 CO2 )2 ·3H2 O, PbCl2, and CH3 NH3 I.